Nicotine engages a VTA-NAc feedback loop to inhibit amygdala-projecting dopamine neurons and induce anxiety-like behaviors - Tïnaïg Le Borgne; Claire Nguyen; Eléonore Vicq; Joachim Jehl; Clément Solié; Nicolas Guyon; Louison Daussy; Aylin Gulmez; Lauren M. Reynolds; Sarah Mondoloni; Stéfania Tolu; Stéphanie Pons; et al. (Nature Communications)
Abstract Nicotine activates ventral tegmental area (VTA) dopaminergic (DA) neurons projecting to the nucleus accumbens (NAc) to drive its reinforcing effects. Simultaneously, nicotine inhibits those projecting to the amygdala (Amg) to mediate anxiety-like behavior through a process that remains unknown. Here, we show that in male mice, NAc- and Amg-projecting DA neurons respond with similar polarities to ethanol and nicotine, suggesting a shared network-based mechanism underlying the inhibitory effect of these otherwise pharmacologically-distinct drugs. Selective activation of NAc-projecting DA neurons, using genetic or optogenetic strategies, produced inhibition of Amg-projecting DA neurons, through a GABAergic feedback loop. Furthermore, optogenetically silencing this feedback loop prevented nicotine from inducing both inhibition of DA neurons and anxiety-like behavior. Therefore, nicotine-induced inhibition of the VTA-Amg DA pathway results from a VTA-NAc inhibitory feedback loop, mediating anxiety-like behavior.